Creatine supplementation does not influence the ratio between intracellular water and skeletal muscle mass in resistance-trained men - Ribeiro, A. S.; Avelar, A.; Kassiano, W.; Nunes, J. P.; Schoenfeld, B. J.; Aguiar, A. F.; Trindade, M. C. C.; Silva, A. M.; Sardinha, L. B.; Cyrino, E. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The authors aimed to compare the effects of creatine (Cr) supplementation combined with resistance training on skeletal muscle mass (SMM), total body water, intracellular water (ICW), and extracellular water (ECW) in resistance-trained men as well as to determine whether the SMM/ICW ratio changes in response to the use of this ergogenic aid. Twenty-seven resistance-trained men received either Cr (n = 14) or placebo (n = 13) over 8 weeks. During the same period, subjects performed two split resistance training routines four times per week. SMM was estimated from appendicular lean soft tissue assessed by dual-energy X-ray absorptiometry. Total body water, ICW, and ECW were determined by spectral bioelectrical impedance. Both groups showed improvements (p < .05) in SMM, total body water, and ICW, with greater values observed for the Cr group compared with placebo. ECW increased similarly in both groups (p < .05). The SMM/ICW ratio did not change in either group (p > .05), whereas the SMM/ECW ratio decreased only in the Cr group (p < .05). A positive correlation was observed (p < .05) between SMM and ICW changes (r = .71). The authors` results suggest that the increase in muscle mass induced by Cr combined with resistance training occurs without alteration of the ratio of ICW to SMM in resistance-trained men.